Evaluation of ozone therapy as an adjunct to the management of otitis externa in dogs - Hareeshma Babu; Laiju M. Philip; Syam K. Venugopal; S. Anoop; C. Jayakumar (Journal of Veterinary and Animal Sciences)
A study was conducted in twelve dogs showing at least two signs of otitis externa, to evaluate the efficacy of ozone therapy in treatment of otitis externa in dogs. The selected dogs were randomly divided into two groups with six animals each. Group I underwent otic flushing with 0.9 per cent normal saline under general anaesthesia, while the other group was treated with 55 μgmL ozonated distilled water in the same manner. All the animals received antibiotic therapy based on the results of antibiogram of otic discharge, along with topical antibiotic and antifungal therapy. Maximum reduction in otitis index score, pruritus severity scale and pain severity score were achieved by day 21 of treatment in all the animals. Radiographically ear canal appeared air filled and widened on fourth week of treatment, suggestive of absence of exudate and oedema in both groups. On clinical and otoscopic examination ulcerations, oedema, erythema, pain and otorrhea was found to be reduced by second week of treatment in Group I, compared to third week in Group I. Even though there was reduction in total viable bacterial count between day one and day seven of treatment in both groups, a marked reduction was observed by day 14 in Group II. Hence, ozone therapy may be considered as an adjunct to the management of otitis externa in dogs along with systemic and topical antibiotic therapy.